Kinetics of microbial protein production and in vitro digestibility of straw ammoniated and/or supplemented with NPN and protein - SINGH, G P; KLOPENSTEIN, T J (The Indian Journal of Animal Sciences, 2013)
IVDMD, IVOMD and microbial protein synthesis kinetics of untreated wheat straw, untreated wheat straw + urea, 3% ammoniated straw and ammoniated wheat straw + casein were determined using rumen liquor of animal fed corn cob and alfalfa. Supplementation of urea increased the IVDMD and IVOMD significantly (P<0.01) overuntreated straw alone. However, ammoniation of straw resulted in significantly higher in vitro digestibility and supplementation of casein to ammoniated straw further increased the digestibility of both DM and OM. Microbial protein contents were increased up to 36 hr on incubation of wheat straw, ammoniated wheat straw and ammoniated wheat straw + casein, but in case of wheat straw + urea the increase was up to 48 hrthereafter declined on all the treatments. The intercept of microbial protein synthesis was incrcased significantly due to ammoniation, however, supplementation of urea to wheat stra w and casein to ammoniated wheat straw did not result in any significant effect. Microbial protein synthesis rates were 3.863,4.496,4.388 and 4.461 mg/hr/g substrate on untreated wheat straw, wheat straw + urea, ammoniated wheat straw and ammoniated wheat straw + casein respectively.